ANALISIS BUTIR SOAL ULANGAN AKHIR SEMESTER MATA PELAJARAN BAHASA INDONESIA SMP NEGERI 7 PALEMBANG - Muchti, Andina; Mayrita, Hastari (Jurnal Ilmiah Bina Edukasi, 2017)
This research is a qualitative descriptive research that aims to describe item UAS students class IX SMPN 7 Palembang viewed from the level of difficulty questions, distinguishing power, and test the validity of the item. Data in the form of student values taken from the answer sheet UAS Indonesian Class IX lesson SMPN 7 Palembang. The results obtained, that is based on the level of difficulty there are 35 questions entered in the category of easy, 11 questions entered in the category of moderate, and 4 problems entered in the difficult category. Based on the differentiation of the problem, there are 0 problems that fall into the category of good, 9 questions that fall into the category is good enough, 41 problems that fall in the bad category with the percentage of the power of differentiation of the problem, falling into the category less good, because 82% of the difference power index entry in good enough criteria. Based on the criteria of question validity, the results indicate that there is 1 question included in the category of validity there are 29 problems that fall into the category of unvalidity.